Workplace based assessment in obstetrics and gynecology clerkship to detect learning gaps - Coelho, Raquel Autran (2019)
Background: An outcome-based curriculum helps to communicate expectations of performance to students and clinical teachers. The Mini Clinical Evaluation Exercise (mini-CEX) is a useful tool for workplace-based formative assessment. The objective of this study was to use workplace-based assessment and student feedback to evaluate an Obstetrics and Gynecology (Ob&Gyn) clerkship curriculum. Methods: A cross-sectional study was conducted with faculty members and medical students in an Ob&Gyn clerkship. The Mini-CEX was introduced into the clerkship assessment system, together with multiple choice question (MCQ) tests. This tool evaluates the history collection, physical examination, clinical judgment, professionalism and humanism, and also gives an overall score at the end of the test. At the end of the rotation, questionnaires were used to collect the students’ perceptions about their skills acquisition during the program. The results of the Mini-CEX, the MCQ test, and questionnaire responses were compared, to determine the extent to which learning objectives were achieved. Results: three faculty members assessed 84 medical students using the mini-CEX during the four-month clerkship. The scores for the physical examination and clinical judgment skills were lower, compared to those of the interviewing skills. Based on the students’ feedback, ratings for physical examination and counseling preparation were rated as “inadequate”, especially for the topic breaking bad news. The bivariate correlation between the mini-CEX skills and MCQ test scores showed a positive relationship (r = 0.27). Although they assess different skills on the Muller pyramid, there appears to be a relationship between “Knowing” and “Doing”. These findings will help curriculum managers to identify important gaps in the rotation design and delivery. Based on these results, training in the skills workshop during the first month of the rotation was initiated, in addition to previous simulated training during the third year of medical course. Conclusions: The introduction of the mini-CEX offers critical information to identify and refine important curriculum elements in the clinical years. Based on this, physical examination and communications skills training were initiated in the skills workshop.